Correlation of Vapor-Liquid Equilibrium for non ideal systems using infinite pressure mixing rules - Abdullah, Mahmoud O.; Hameed, Venus M.; Hussein, Maha A. (Nahrain University College of Engineering Journal, 2012)
Isothermal vapor-liquid equilibrium data of five groups, which are polar-polar at low and high pressure, polar-non polar at low and high pressure, and non polar-non polar at high pressure were investigated. Each group of these contains four binary mixtures with 334 overall data points. By using PRSV-EOS withWS and HVOS mixing rules at infinite pressure where ? G obtained by adopting UNIQUAC and Wilson models. These mixing rules have many advantages and can handle all the systems with good accuracy. Noting that WS mixin rules have one adjustable parameter and HVOS mixing rules without adjustable parameter. Many efforts to modify the results were made. The best modification which gives the more accurate results for all groups is the introduction of a new constantvalue „C? which is specified for each system in HVOS mixing rules with quadratic mixing rules with one adjustable parameter hij.